Elevasi Kepala 30° Terhadap Peningkatan Saturasi Oksigen Pada Pasien Stroke - Mulyani, Tri; Iksan , Ricky Riyanto; Yeni, Roza Indra (Borneo Nursing Journal (BNJ), 2026)
Stroke is an acute neurological disease that can cause oxygenation disturbances due to neurological dysfunction, impaired airway protection, and ventilation abnormalities, which may lead to decreased peripheral oxygen saturation (SpO₂). A 30° head-up position is a simple nursing intervention that may improve pulmonary ventilation, enhance gas exchange, and maintain oxygenation in stroke patients. This study aimed to determine the effect of a 30° head-up position on improving oxygen saturation among stroke patients. Methods: This Evidence-Based Nursing (EBN) implementation used a quasi-experimental design with a pre-test and post-test approach involving four stroke patients admitted to Hospital X from May 11–14, 2026. Respondents were selected based on inclusion criteria, including patients diagnosed with stroke, hemodynamically stable conditions, and measurable oxygen saturation using pulse oximetry. The intervention consisted of providing a 30° head-up position. Oxygen saturation was measured before and after the intervention. Data were analyzed using the paired t-test. Results: Before the intervention, all respondents (100%) had oxygen saturation levels below 90%, with a mean value of 89.10 ± 0.68. After receiving the 30° head-up position, all respondents (100%) had oxygen saturation levels above 90%, with the mean value increasing to 99.70 ± 0.79. Statistical analysis showed a significant difference in oxygen saturation before and after the intervention (p = 0.021). Conclusion: The 30° head-up position significantly improved oxygen saturation in stroke patients. This intervention can be applied as a simple, safe, and evidence-based nursing intervention to support optimal oxygenation management in stroke patients.